Evidence of a strong paleoearthquake in ∼9.1 ka cal BP interpreted from mass transport deposits, western Quebec – northeastern Ontario, Canada. (15th April 2020) - Brooks, Gregory R.
Abstract : This paper reviews and expands upon stratigraphic and chronologic evidence supporting the interpretation of a strong, early postglacial paleoearthquake in western Quebec-northeastern Ontario, Canada. Event horizon mapping at Dasserat, Dufresnoy and Duparquet lakes, Quebec, coring at Chassignolle and Malartic lakes, Quebec, analysis of varve exposures near both the Twin Falls and Frederick House dams, Ontario, and review of published and unpublished logs of varve exposures, reveal that mass transport deposits formed in, or are inferred to have formed in, varve year (vyr) 1483 (relative to the Timiskaming varve series, and about 9.1 ka cal BP) are present at numerous locations within the study area. The spatial extent of the vyr 1483 mass transport deposit signature covers at least 14, 600 km 2, and is best explained by shaking from a paleoearthquake. The magnitude of the event is estimated to be a minimum of M ∼7.3, which is indicative of a strong paleoearthquake. The vyr 1483 paleoearthquake is one of 11 events of ≥M ∼5, occurring within a 425 varve year period between ∼9.4 and 8.95 ka cal BP, and is likely part of a period of elevated, early postglacial, seismicity associated with rapid crustal unloading. The absence of an equivalent signature within the younger portion of the glaciolacustrine or lacustrine deposits in local lakes, implies that this paleoearthquake is the strongest to occur within the study area since about 9.1 ka cal BP. The highly-precise correlation of widely-spaced mass transport and disturbed deposits provided by varves is essential to the paleoearthquake interpretation. Highlights: Widespread mass transport deposits formed in a common varve year. Located over at least 14, 600 km 2 of low seismically active area of Canadian Shield. Failure signature is best explained by paleoearthquake of minimum magnitude M ∼7.3 Paleoearthquake is likely strongest within study area since about 9.1 ka cal BP.